Effect of MnFe2O4 magnetic nanoparticle addition rate on the structure and properties of magnetic hollow hydroxyapatite microspheres - Rong, Mayifei; Deng, Shuangshuang; Liu, Dingge; Zhang, Xin; Xu, Xiaoguang (Frontiers in Nanotechnology, 2026)
Magnetic hollow hydroxyapatite (HAp) microspheres have demonstrated great potential for biomedical applications and pollution treatment. However, it remains unclear how the rate of magnetic nanoparticle addition during synthesis affects the material’s structure and properties. In this study, samples with varying magnetic nanoparticle addition rates were prepared and analyzed. The results reveal that the rate of magnetic nanoparticle addition is associated with the composition, structure, and properties of magnetic hollow hydroxyapatite microspheres. The sample with a medium magnetic nanoparticle addition rate exhibits optimal composition and structure. The saturation magnetization of the optimal sample is 18.99 emu/g, and the specific surface area and pore volume are 61.66 m2/g and 0.17 cm3/g, respectively. This research provides valuable guidance for synthesizing magnetic hollow hydroxyapatite microspheres and offers insights into the development of other magnetic composite materials.